2008
DOI: 10.1002/biot.200700238
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopy analysis of the conformational quality of recombinant proteins within inclusion bodies

Abstract: The solubility of recombinant proteins produced in bacterial cells is considered a key issue in biotechnology as most overexpressed polypeptides undergo aggregation in inclusion bodies, from which they have to be recovered by solubilization and refolding procedures. Physiological and molecular strategies have been implemented to revert or at least to control aggregation but they often meet only partial success and have to be optimized case by case. Recent studies have shown that proteins embedded in inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 59 publications
2
44
0
Order By: Relevance
“…Thus, the specific biological activity rather than the presence of the protein species in the soluble cell fraction reveals the conformational quality of the product and, therefore, its biotechnological potential. In this regard, an increasing number of structural analyses reveal the coexistence, in the embedded protein species, of a cross-␤-sheet-based, amyloidlike organization (3) and also that of a native secondary structure (5). In inclusion bodies formed by enzymes, the associated enzymatic activity is sufficient for efficient in situ substrate processing.…”
mentioning
confidence: 99%
“…Thus, the specific biological activity rather than the presence of the protein species in the soluble cell fraction reveals the conformational quality of the product and, therefore, its biotechnological potential. In this regard, an increasing number of structural analyses reveal the coexistence, in the embedded protein species, of a cross-␤-sheet-based, amyloidlike organization (3) and also that of a native secondary structure (5). In inclusion bodies formed by enzymes, the associated enzymatic activity is sufficient for efficient in situ substrate processing.…”
mentioning
confidence: 99%
“…One of the vibrational bands visibly altered in both dead HeLa -and Vero cells (but only significantly altered in Vero cells) was the appearance of the band at 1626 cm -1 . This band was assigned to intermolecular β-sheet protein-protein interactions suggestive of protein compactness and the degree of protein aggregation (Doglia et al, 2008). Zelig et al (2009) found that a decrease in α-helices and an increase in β-sheets were indicative of apoptosis and that the degree of β-sheets could be linked to the stage of apoptosis (Zelig et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Spectral techniques such as Fourier transform infrared spectroscopy (FTIR) (1,2,16) and nuclear magnetic resonance (NMR) (3) revealed different folded forms in preparations from IBs. This indicates that there are differences in structure of proteins isolated from IBs compared to those expressed solubly (4).…”
Section: Introductionmentioning
confidence: 99%
“…Cell free growth (in lysates), or expression in yeast, insect cells or transfected mammalian cells are all possible alternatives. While expression systems in yeast (10,11) such as Pichia pastoris (12)(13)(14)(15) and the baker's yeast Saccharomyces cerevisiae (16) are inexpensive and well developed, eukaryotic or insect cell culture methods are significantly more expensive than bacterial. Stably transformed higher eukaryotic cell lines are given to variability, tests for expression tests are time consuming, and the scale-up can be quite difficult.…”
Section: Introductionmentioning
confidence: 99%